2003
DOI: 10.1023/a:1023791229361
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Peritoneal carcinomatosis had a wider distribution when mucinous fluid was present; this cancer distribution by intraperitoneal fluid hydrodynamics occurred regardless of histologic aggressiveness. The organs that have peritoneal fluid resorption (omentum and omental appendages) have a high incidence of implants. Small bowel and its mesentery free to move by peristalsis had a reduced incidence of implants as compared to the ileocecal area, which is fixed to the retroperitoneum. These observations may facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…The distribution of DSRCT is similar to the peritoneal surface malignancies such as malignant peritoneal mesothelioma and papillary serous adenocarcinoma of women [20]. The pelvis was the most common site for the disease, especially for large volume disease.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of DSRCT is similar to the peritoneal surface malignancies such as malignant peritoneal mesothelioma and papillary serous adenocarcinoma of women [20]. The pelvis was the most common site for the disease, especially for large volume disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was assumed that intraperitoneal cancer dissemination was a random process independent of the physical and biological properties of the tumor and the host[80]. However, several studies report that the direction taken by the loose tumor cells and their ultimate destination are dependent on the anatomic site of the primary tumor and the continued cephalic circulation responsible for the clearance of fluid from the peritoneal cavity[81-83]. The latter is due to changes in intra-abdominal pressure during respiration, gravity and peristalsis of the bowel; which results in a clockwise flow from the pelvis, along the right paracolic gutter and to the subdiaphragmatic space and finally towards the pelvis again[40,81].…”
Section: Pathophysiology Of Colorectal Pcmentioning
confidence: 99%
“…The most common identified metastatic sites are including the pelvic wall, omentum and mesentery, though there are other adjacent metastatic sites have also been reported such as skin and lymph nodes (Cheng et al, 2009). Ovarian tumor cells spread through the peritoneal fluid or known as transcoelomic route of metastasis from the pelvic up to intestinal mesentery that allows for implantation of the tumors to different peritoneal organs (Meyers et al, 1987; Coakley and Hricak, 1999; Carmignani et al, 2003; Nougaret et al, 2012; Le, 2013). Though, this implantation of tumors depends on the fluidity of the peritoneum in which less fluidity will restrict the movement of the tumor cells at the primary site (Carmignani et al, 2003; Tan et al, 2006; Feki et al, 2009), thus may results in the accumulation of ascites in the abdomen.…”
Section: Mir-200c-mediated Metastasismentioning
confidence: 99%
“…Ovarian tumor cells spread through the peritoneal fluid or known as transcoelomic route of metastasis from the pelvic up to intestinal mesentery that allows for implantation of the tumors to different peritoneal organs (Meyers et al, 1987; Coakley and Hricak, 1999; Carmignani et al, 2003; Nougaret et al, 2012; Le, 2013). Though, this implantation of tumors depends on the fluidity of the peritoneum in which less fluidity will restrict the movement of the tumor cells at the primary site (Carmignani et al, 2003; Tan et al, 2006; Feki et al, 2009), thus may results in the accumulation of ascites in the abdomen. The formation of ascites is not well understood, yet previous studies have shown that ascites accumulation is regulated by VEGF (Kraft et al, 1999; Xu et al, 2000), a validated target of miR-200c, and ascetic fluid is primarily composed of tumor cells, white blood cells and lactate dehydrogenase (Runyon et al, 1988; Bansal et al, 1998; Feki et al, 2009; Kalogeraki et al, 2012).…”
Section: Mir-200c-mediated Metastasismentioning
confidence: 99%